2012
DOI: 10.1111/j.1365-2826.2011.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Exercise and Training on the Circulating Concentration of Prolactin in Humans

Abstract: Physical activity has an impact on several endocrine functions. During exercise, certain endocrine adjustments are required to maintain the homeostasis. It is well known that, depending on the intensity and duration, exercise stimulates the release of the hormone prolactin (PRL). After the cessation of acute exercise, this effect persist and continues during the recovery period. Chronic exercise can affect the PRL basal concentration and/or the PRL response to acute exercise. The main functions of PRL are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 70 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, previous studies have shown an increase in prolactin (PRL) induced by exercise (Gray et al, 1993 ; Hickson et al, 1994 ; Kraemer et al, 1998 ), which appears to be related to the intensity of exercise (Luger et al, 1992 ). However, there is controversial literature about the changes of resting and exercise-induced PRL concentration and its association to overtraining states (Rojas-Vega et al, 2011 ). Growth hormone (GH) and its primary downstream mediator, insulin-like growth factor I (IGF-I), play an important role in formation, maintenance, and regeneration of skeletal muscles (Frystyk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have shown an increase in prolactin (PRL) induced by exercise (Gray et al, 1993 ; Hickson et al, 1994 ; Kraemer et al, 1998 ), which appears to be related to the intensity of exercise (Luger et al, 1992 ). However, there is controversial literature about the changes of resting and exercise-induced PRL concentration and its association to overtraining states (Rojas-Vega et al, 2011 ). Growth hormone (GH) and its primary downstream mediator, insulin-like growth factor I (IGF-I), play an important role in formation, maintenance, and regeneration of skeletal muscles (Frystyk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…[167] Most of the patients with RA suffer from impaired muscle function such as (or including) imbalance and reduced muscle strength. [8] The symptoms of RA, such as joint swelling, pain, stiffness, and other complications, may hamper the physical training and reduce physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that physical exercise can have powerful acute effects on hormonal release ( Galbo, 1983 ; Hackney and Lane, 2015 ). In this regard, exercise-induced increases in blood cortisol ( Galbo, 1983 ), prolactin ( Hackney, 2008 ; Rojas Vega et al, 2012 ), and VEGF ( Kadi, 2005 ) levels have been well documented. Interestingly, in the present study, statistically significant increases in cortisol concentrations were only observed in the group performing HIIT under hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant correlation was observed between changes in blood lactate concentrations and prolactin only under the hyperoxic condition. Changes of prolactin may be of interest because of its multiple regulatory effects on reproduction, homeostasis, growth and development as well as immunoregulation, all of which are essential components of physiological and morphological training adaptations ( Hackney et al, 2016 ; Rojas Vega et al, 2012 ). Prolactin seems to be released in response to various forms of stress, including, but not limited to, exercise ( Strüder et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%